The Pengaruh Indeks Pembangunan Manusia, Opini Audit, Kompleksitas Pemerintah dan Kekayaan Daerah Terhadap Pengungkapan Informasi Keuangan pada Website Resmi Pemerintah Daerah Studi Kasus pada Pemerintah Provinsi di Indonesia Tahun 2020 - Nathasya Prissillya Aggatha; Sri Rahayu; Wahdan Arum Inawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This research was conducted to determine whether human development index, audt opinions, government complexity, and regional wealth have an effect on disclosure of financial information on the regional governments official website in Indonesia. The saturated sample technique was applied in sample collection, and the sample in this research covers all provincial governments in Indonesia in 2020. This research applies multiple linear regression analysis using IBM SPSS version 26 software. The research findings confirm that the human development index, audit opinion, government complexity, and regional wealth all have a simultaneous impact on the disclosure of financial information. Meanwhile, partially only regional wealth variables have an impact on the disclosure of financial information on the official websites of local governments throughout all provinces in Indonesia in 2020.